Acute and subacute toxicity evaluation of ethanolic extract from fruits of schinus molle in rats - Ferrero, Adriana Alicia (2007)
Ethanolic and hexanic extracts from fruits and leaves of Schinus molle showed ability to control several insect pests. Potential vertebrate toxicity associated with insecticidal plants requires investigation before institutional promotion. The aim of the present study was to evaluate the acute and subacute toxicity of ethanolic extracts from fruits of Schinus molle in rats. The plant extract was added to the diet at 2 g/kg body weight/day during 1 day to evaluate acute toxicity and at 1 g/kg body weight/day during 14 days to evaluate subacute toxicity. At the end of the exposure and after 7 days, behavioral and functional parameters in a functional observational battery and motor activity in an open field were assessed. Finally, histopathological examinations were conducted on several organs. In both exposures, an increase in the arousal level was observed in experimental groups. Also, the landing foot splay parameter increased in the experimental group after acute exposure. Only the subacute exposure produced a significant increase in the motor activity in the open field. All these changes disappeared after 7 days. None of the exposures affected the different organs evaluated. Our results suggest that ethanolic extracts from fruits and leaves of Schinus molle should be relatively safe to use as insecticide.